Approach to chondromalacia patellae: An integrative literature review (Research, Society and Development, 2023)
Introduction: Chondromalacia patellae is a disease that compromises the patient's quality of life and well-being. It has a multifactorial etiology and an important clinical picture, mainly due to episodes of pain and limited joint movement. Objective: The aim of this study was to evaluate the clinical, epidemiological and pathophysiological aspects of chondromalacia patellae, building knowledge based on case reports and theoretical components on the subject. Materials and Methods: This is an integrative literature review on the general clinical characteristics of chondromalacia patellae. The PICO strategy was used to develop the guiding question. In addition, the descriptors "Chondromalacia Patellae"; "Epidemiology"; "Therapeutics" were cross-referenced in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar and Virtual Health Library (VHL) databases. Results and Discussion: A significant proportion of the articles discussed the etiologies and clinical picture of chondromalacia patellae, highlighting the importance of mechanical stress in the pathogenesis and emphasizing the impact of patellofemoral pain on patients' lives. In addition, the studies postulated that the diagnosis of this chondropathy is made clinically and by imaging methods, in order to direct the therapeutic plan, whatever it may be, taking into account the patient's singularities. Conclusion: In view of the aspects discussed, it can be seen that chondromalacia patella significantly affects a large portion of the population, and it is necessary to develop new ways of managing the disease in order to improve the care offered to individuals.